IMPLEMENTATION OF THE WORK PLAN BETWEEN BADAN KEAMANAN LAUT REPBULIK INDONESIA AND THE U.S. COAST GUARD - Sari, Helen Juwita; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research analyzes how the implementation of the work plan between the Maritime Security Agency of the Republic of Indonesia and the United States Coast Guad (USCG). Indonesia as a country which is the fulcrum of two oceans, has an obligation to build maritime strength, in order to maintain maritime sovereignty and wealth as well as a form of state responsibility in maintaining shipping safety and maritime security. This is also in line with Indonesia's Vision, namely the Vision of Becoming a World Maritime Axis. There are many maritime threats such as IUU (Illegal Unregulated Unreported Fishing), transnational crimes, separatism, as well as territorial violations and border conflicts. One of Indonesia's efforts to overcome this is to form a Maritime Security Agency. To increase Bakamla's capability, maritime security cooperation was carried out with the United States, in this case cooperation between Bakamla and USCG. This research uses qualitative research methods, with data collection techniques, namely literature studies originating from books, journals, reports, documents, newspapers, internet sites, and reports. This study uses the perspective of Neorealism and the theory of International Cooperation and the concept of Policy Implementation. The implementation of the work plan between Bakamla and USCG went well and the activities carried out were in accordance with the contents of the work plan. There is a decrease in the number of violations at sea which is evidence of an increase in maritime security and safety in Indonesia. Keywords: World Maritime Axis, Bakamla, USCG